A sustentabilidade com a recuperação e valorização de cacos e casqueiros provenientes de mármore e granito - Bernardi, Vinícius Freisleben (2014)
The purpose of the present survey was to assess the contribution from the recovery and valorization of wastes to the corporative sustainability. Therefore, the sustainable management of rests from marble and granite industry was assessed. This work contributes mainly through the sustainability indicators selection from the current scientific knowledge and the sustainability assessment by means of the indicators selected in the first part in the recovery and valorization of marble and granite residues. Methodologically, a bibliometric review on the scientific production about sustainability indicators has been carried out focusing wastes management, in order to select tools to assess the marble and granite wastes management’s sustainability. Next, the wastes generation was diagnosed in a compilation of primary information about wastes-handling using the indicators selected in the bibliometric review to assess the impact of rests-recovery and -valorization in the marble and granite industry. Two wood businesses (S1 and S2) and two marble businesses (M1 and M2) have been selected for this study. This research provides relevant information about the scientific production on the subject sustainability assessment, systemizing important data regarding wastes management and the impacts of wastes management in marble and granite businesses.